Long term changes and recent state of macrozoobenthic communities along the Bulgarian Black Sea coast - TODOROVA, V.; KONSULOVA, T. (Mediterranean Marine Science, 2000)
The analysis of macrozoobenthic samples collected from 34 stations along the Bulgarian Black Sea shelf at depths ranging from 12 to 83 m yielded 103 taxonomic units. The average abundance established in the present study was over 5000 ind/m2 with nearly 70% dominance of the polychaetes. The number of species, Shannon-Wiener diversity index (H') and Pielou's evenness (J) were the lowest in Varna and Burgas bays, indicating that they are the most ecologically threatened areas along the Bulgarian Black Sea coast. The quantitative and qualitative data were compared to published data from the pristine period 1954-1957 and from the period 1982-1985 with intensive anthropogenic pressure. The comparison revealed an increase of the share of molluscan species and a decrease of the contribution of crustacean species in the total number of species. A 7-fold increase of the total average abundance was established compared to the pristine period 1954-1957. During the recent period the polychaetes are the most dominant group in the benthic abundance, while during the pristine period 1954-1957 the most abundant were the molluscs with nearly 61% of the total abundance. These changes in the benthic communities are attributed to the process of eutrophication. While in the pelagic environment signs of recovery have been observed, we deem that up to 1997 no such signs are valid for the benthic communities.